The Influence of Product Quality, Distribution Channels and Customer Satisfaction on Purchasing Decisions of TOA Paint at PT Medan Warna Abadi - Hendry; Shelly (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to test and analyze the effects of Product Quality, Distribution Channels and Customer Satisfaction on the TOA Paint Purchase Decision at PT Medan Warna Abadi. The decline in purchasing decisions can be seen from not achieving sales targets. The product quality has decreased, which has triggered customer complaints. Distribution channels that are not optimal. Decreased customer satisfaction. The approach in this research is a quantitative approach. In this study, researchers used quantitative descriptive research methods. The total population of 149 customers and the sample in this study were all customers as many as 109 employees and used a sample collection technique, namely saturated sampling. The analyst method uses validity and reliability testing, classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results of the calculation of the partial hypothesis testing Product Quality, Distribution Channels and Customer Satisfaction have a positive and significant effect on the TOA Paint Purchase Decision at PT Medan Warna Abadi and simultaneously Product Quality, Distribution Channels and Customer Satisfaction have a positive and significant effect on the TOA Paint Purchase Decision at PT Medan Warna Abadi